Perception of edges and visual texture in the camouflage of the common cuttlefish, Sepia officinalis - Zylinski, S. (The Royal Society, 2008)
The cuttlefish, Sepia officinalis, provides a fascinating opportunity to investigate the mechanisms of camouflage as it rapidly changes its body patterns in response to the visual environment. We investigated how edge information determines camouflage responses through the use of spatially high-pass filtered ‘objects’ and of isolated edges. We then investigated how the body pattern responds to objects defined by texture (second-order information) compared with those defined by luminance. We found that (i) edge information alone is sufficient to elicit the body pattern known as Disruptive, which is the camouflage response given when a whole object is present, and furthermore, isolated edges cause the same response; and (ii) cuttlefish can distinguish and respond to objects of the same mean luminance as the background. These observations emphasize the importance of discrete objects (bounded by edges) in the cuttlefish's choice of camouflage, and more generally imply that figure–ground segregation by cuttlefish is similar to that in vertebrates, as might be predicted by their need to produce effective camouflage against vertebrate predators.